INFLUENCE AGAINST RECEIVABLE MANAGEMENT CAPABILITIES IN PRODUCING INCOME ON THE BASIC INDUSTRY AND CHEMICAL COMPANY SUB SECTOR FEED LISTED IN INDONESIA STOCK EXCHANGE - Edhi Asmirantho; Resta Rosdiana (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2018)
This study was conducted to determine and demonstrate empirically the effect of accounts receivable management of the company's ability to generate profits on the company grounds and chemical industry subsectors recorded fodder in the Indonesia Stock Exchange. Each company has a complete data for 10 years in the period 2004 to 2013. Technical analysis of using multiple regression analysis, the data processing using SPSS version20. The results showed receivable management firm base and chemical industry subsectors fodder IDX can be said is still not optimal. Receivables management fluctuating and rising slowly apparent from the Receivable Turnover (RTO), Receivable Turnover in Days (RTD) and Total Asset Turnover (TATO) are unstable and there are accounts receivable with a long lifespan. Based on the R-square is formed, the independent variables are able to explain the growth of return on investment of 69.3%. Hypothesis testing using the F test showed F count F table (19.579 2.975) with a significance value of 0.000 0.05 indicates that Receivable Turnover, Receivable Turnover in Days and Total Asset Turnover simultaneously significant effect on Return on Investment. While testing the hypothesis using the t test showed the value Receivable Turnover (1.642 2.056) with significant value 0.113 0.05 and Receivable Turnover in Days (1.547 2.056) with significance 0.134 0.05 where t t table and the value significant 0.05, which indicates that they do not affect the return on investment, while the Total Asset Turnover value condition t t table (6.520 2.056) and a significant value 0.000 0.05 indicates that positive and significant effect on Return on Investment.Keywords: Activity, Profitability, Receivable Turnover, Receivable Turnover in Days, Total Asset Turnover, Return on Investment.